Biological applications of synthetic anion transporters. Issue 91 (15th October 2020) - Akhtar, Nasim; Biswas, Oindrila; Manna, Debasis
Abstract : Transmembrane transport of anions by small molecules has recently been used to reduce the viability of cancer cells and fight against antibiotic-resistant and clinically relevant bacterial strains. Abstract : The use of synthetic ion transporters for alteration of the concentration of ions across cell membranes has drawn attention from scientists over the last two decades. This ion transport property has been sensibly used to reduce the viability of cancer cells mainly due to the disruption of their ion homeostasis, leading to the perturbation of their abnormal pH gradient. The use of the proanionophore strategy has been recently adopted to increase cellular deliverability and reduce unwanted cytotoxicity towards normal cells. Meanwhile, various anionophores exhibiting non-toxic behavior in epithelial cells have shown a great propensity to be used as a putative treatment for channelopathies like cystic fibrosis. Anionophores with Cl − ion transport mediated antibacterial activities have also been successfully used against clinically relevant bacterial strains, many of which are tolerant towards commercial antibiotics. Recent developments in the chloride ion transport mediated biological activities of anionophores have been mainly discussed in this article. It also highlights other aspects, such as design criteria, targeted delivery options, and others, which can be useful for the further development of selective anionophores for specific biological applications.